ARTS ASSOCIATED WITH THE PRIMARY RHYME IN AGAHI’S QASIDAS: RADD AL-QAFIYAH AND TAWSIM - Hikmat Sultonovich Yusupov (International Journal of Literature and Language Studies, 2026)
This article examines the poetic devices of radd al-qafiyah and tawsim, both associated with the primary rhyme, as employed in Agahi’s qaṣidas. Through an analysis of these rhetorical devices, the study demonstrates the poet’s exceptional artistic craftsmanship and poetic mastery.